2012
DOI: 10.1039/c2nr30222e
|View full text |Cite
|
Sign up to set email alerts
|

N,N-Dimethylformamide-stabilized gold nanoclusters as a catalyst for the reduction of 4-nitrophenol

Abstract: In this study, we investigated the catalytic properties of N,N-dimethylformamide (DMF)-stabilized gold nanoclusters (AuNCs) in the reduction of 4-nitrophenol (PNP) to 4-aminophenol by NaBH(4), a well known model reaction to be catalyzed by metal surfaces. The DMF-stabilized AuNCs were prepared in DMF by a surfactant-free method. The DMF-stabilized AuNCs showed high catalytic activity even when used in small quantities (∼10(-7) g). The pseudo-first-order rate constant (k(app)) and activation energy were estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(147 citation statements)
references
References 39 publications
9
138
0
Order By: Relevance
“…The effect of the second metal in the catalysis will be extensively explored in our on-going project. Compared with some previously reported anisotropic gold nanoparticles [2,[37][38][39][40][41][42], the present gold nanostars (with kapp = 4.36 min −1 ) presented better catalytic activity than that of gold nanocages (with kapp = 2.83 min −1 ) [33] and gold nanoantennas (with kapp = 1.61 min −1 ) [13] for the reduction of 4-NP at room temperature. Moreover, compared with some previously reported gold nanoparticles capped with macrocycles (e.g., cyclodextrin, calixarene, and cucurbiturils) [32,43,44], cucurbituril- The k app values were then correlated to the inverse temperature, and we calculated the apparent activation energies (E a ) based on the Arrhenius equation ( Figure S4 and Table 1) [13,33].…”
Section: Resultsmentioning
confidence: 87%
“…The effect of the second metal in the catalysis will be extensively explored in our on-going project. Compared with some previously reported anisotropic gold nanoparticles [2,[37][38][39][40][41][42], the present gold nanostars (with kapp = 4.36 min −1 ) presented better catalytic activity than that of gold nanocages (with kapp = 2.83 min −1 ) [33] and gold nanoantennas (with kapp = 1.61 min −1 ) [13] for the reduction of 4-NP at room temperature. Moreover, compared with some previously reported gold nanoparticles capped with macrocycles (e.g., cyclodextrin, calixarene, and cucurbiturils) [32,43,44], cucurbituril- The k app values were then correlated to the inverse temperature, and we calculated the apparent activation energies (E a ) based on the Arrhenius equation ( Figure S4 and Table 1) [13,33].…”
Section: Resultsmentioning
confidence: 87%
“…The linear fit indicates that relation of lnk to 1/T follows Arrhenius equation. The active energy (E a ) was derived to be 27.3 kJ mol À1 based on the slop of the linear fitting line, which is lower than [46,[51][52][53][54] or close to [55,56] the E a values reported in the literatures when gold metal nanoparticles were used as catalysts for reduction of 4-NP. It has been demonstrated that the lower the activation energy is, the higher the catalytic activity is [52].…”
Section: Catalytic Propertiesmentioning
confidence: 99%
“…In recent decades, metal nanomaterials have attracted much attention because of their extensive applications in catalysis, [1][2][3] electrooptical devices, [4,5] electronic devices [6,7] and biological sensors. [8] Among various metal particles, copper nanoparticles have been extensively investigated for their promising applications in different fields, such as catalysts, [9][10][11] optical devices, [12][13][14] magnetic devices, [15] antibacterial agents [16,17] and thermal conducting materials.…”
Section: Introductionmentioning
confidence: 99%